1986
DOI: 10.1152/jn.1986.56.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Tooth pulp input to the shell region of nucleus ventralis posteromedialis of the cat thalamus

Abstract: A population of neurons in the somatosensory part of the nucleus ventralis posteromedialis (VPM proper) that responded to electrical stimulation of the tooth pulp were studied in cats under urethan-chloralose anesthesia. Two classes of units responsive to electrical stimulation of the contralateral canine tooth pulp were identified. One class was responsive only to tooth pulp stimulation and these units were designated as tooth pulp specific (TPS) units. The other class of units responded to mechanical stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In recent years evidence has accumulated to suggest that nociceptive neurones in the cat are located in a ~176 region surrounding the main tactile core of the ventrobasal complex. This appears to be true for VPL (Kniffki and Mizumura 1983;Honda et al 1983;Yokota et al 1988) and VPM, where the shell region region contains nociceptive neurones responding to stimulation of facial skin (Yokota andMatsumoto 1983a, 1983b;Yokota et al 1985) and tooth pulp (Rydenhag and Roos 1986;Yokota et al 1986). …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In recent years evidence has accumulated to suggest that nociceptive neurones in the cat are located in a ~176 region surrounding the main tactile core of the ventrobasal complex. This appears to be true for VPL (Kniffki and Mizumura 1983;Honda et al 1983;Yokota et al 1988) and VPM, where the shell region region contains nociceptive neurones responding to stimulation of facial skin (Yokota andMatsumoto 1983a, 1983b;Yokota et al 1985) and tooth pulp (Rydenhag and Roos 1986;Yokota et al 1986). …”
Section: Discussionmentioning
confidence: 95%
“…If this trigeminal cerebrovascular innervation is involved in nociception and hence in the pathogenesis of headache, then it would be expected that neurones could be similarly activated in the thalamus, probably in areas known to respond to noxious stimulation of other orofacial structures. Numerous electrophysiological studies (for a review see AlbeFessard et al 1985) have revealed trigeminal nociceptive thalamic neurones, including some with input from the teeth, in several nuclear groups: in the intralaminar group of nuclei (Dong et al 1978;Yokota et al 1985;Rydenhag and Roos 1986;Yokota 1988), the posterior group (POm) (Woda et al 1975;Matsumoto et al 1988) and the ventroposteromedial nucleus (VPM) (Yokota andMatsumoto 1983a, 1983b;Yokota et al 1985;Rydenhag and Roos 1986;Yokota et al 1986). Recently two other areas have been increasingly implicated in trigeminal nociception, the ventral periphery of VPM (VPMvp) and nucleus submedius (Craig and Burton 1981;Craig 1987;Dostrovsky et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, lesions specifically of rostral components of the VBSNC or injection into them of analgesic chemicals such as morphine may disrupt some pain behavior, as well as jaw-opening reflex activity, as mentioned in Section III, and there is evidence that caudalis lesions may not completely eliminate all behavioral responses evoked by noxious orofacial stimuli (Graham et al, 1988;Dallel et al, 1989;Duale et al, 1996; and see Sessle, 1987). Also, while it has been reported that caudalis disruption can abolish tooth-pulp-evoked responses in the ventrobasal thalamus (Yokota et a!., 1986), other studies have shown, in contrast, that caudalis lesions are relatively ineffective in affecting thalamic neuronal activity evoked by noxious stimuli applied to intra-oral or peri-oral tissues (Dallel et al, 1988;Raboisson et al, 1989 Despite these findings, the relative contributions of the subnuclei interpolaris and oralis vis-a-vis the subnucleus caudalis are less apparent. The role of nterpolaris is in fact still an enigma.…”
Section: Other Evidencementioning
confidence: 99%
“…A technique comparable to that employed by was used to label relay cells by retrograde transport of horseradish peroxidase (HRP) following injection of enzyme into the portion of the ventral posteromedial thalamic nucleus (VPM) showing maximal evoked response t o stimulation of the maxillary and mandibular canine tooth pulps. The use of this electrophysiological approach was to ensure that the greatest concentration of HRP would be deposited in the medial VPM, an important site of termination of oral and perioral trigeminothalamic relay cells (Albe-Fessard et al, Yokota et al, 1986). It is, of course, not possible strictly to identify which of the relay cells labeled by the injection would be carrying nociceptive transmissions.…”
Section: Introductionmentioning
confidence: 99%